Molecular Docking and in Silico Pharmacokinetic Analysis of Peronemin As A Potential 17β-Hsd1 Inhibitor For Estrogen-Dependent Cancer Therapy - Puspitasari, Ratih Dyah; Tarigan, Indra Lasmana (Universitas Pendidikan Mandalika, 2025)
High levels of estradiol (E2) are important in the development of endometrial cancer. This hormone is mostly produced when the enzyme 17β-hydroxysteroid dehydrogenase type 1 (17β-HSD1) changes estrone (E1) into estradiol (E2). Inhibiting this enzyme can reduce estrogen production in cancers that rely on estrogen. This study examined three Peronemin derivatives (A2, A3, C1) as potential 17β-HSD1 inhibitors through detailed computer analysis. PASS predictions showed these compounds likely have antineoplastic activity (Pa > 0.85). Their physicochemical properties, based on Lipinski's rule, suggest they have good ADME profiles, with high gastrointestinal absorption and a predicted ability to cross the blood-brain barrier.Molecular docking results showed that all three compounds interacted stably with the 17β-HSD1 active site. Peronemin C1 had the strongest binding (ΔG = -6.56 kcal-mol-¹; Ki = 15.56 μM). Mapping the interactions revealed that A2 formed hydrogen bonds with Tyr155, A3 formed hydrogen bonds with Lys159, and C1 exhibited strong hydrophobic interactions. The results suggest that Peronemin A2, A3, and especially C1 could be promising for further development as 17β-HSD1 inhibitors. However, further laboratory studies are needed to confirm the effectiveness of these compounds and determine their practical application.